José María Blázquez, Raquel López Melero y Juan José Sayas, Historia de Grecia Antigua. Madrid, Cátedra, 1989, 1.131 pp., 18 mapas, 84 figs. - García Gelabert, M.P. (Gerión. Revista de Historia Antigua, 1991)
Sin resumen